The role of managerial fit in determining organizational performance: an empirical assessment of Presidents in U.S. higher education - Rutherford, Amanda (2017)
The question of managerial fit?the congruence between a manager and his or her environment?has become widely debated by policymakers, practitioners, and scholars from a number of fields as the occurrence of non-internal management hires has increased across many types of organizations. Although many assume that higher levels of fit in an organization will generate better performance, others argue that misfits are better suited at leading organizations as motivated change agents. In this study, a measure of person?organization fit is created using original cross-sectional time-series data on U.S. university presidents from 1993 to 2009. Findings indicate that maximizing fit is not always ideal and that fit has a nonlinear relationship with organizational performance such that some fit is healthy but high fit can be detrimental for student performance measures. - Reproduced.
Keywords: Education; Managerial fit; Organizational performance